EFFECTIVENESS OF E-WOM ON BRAND RESONANCE - V.ANUPRIYA, Dr.G.S.MAHESWARI,Dr.M.KAVITHAandDr.VINNARASIB (International journal of economic perspectives, 2022)
One of the most comprehensive conceptions of eWOM was proposed by Litvin et al. (2008), who described it as all informal communication via the Internet addressed to consumers and related to the use or characteristics of goods or services or the sellers thereof. When buying products, consumers often look at information written by other consumers on the internet. In other words, they turn to electronic word of mouth (eWOM). Marketers can take steps to generate, support, and amplify eWOM and so influence consumers’ decision-making process.